The Impact of Human Resource Practices and Organizational Climate Towards the High Performance Work Systems - A Case Study of ANGKASA - Abdul Halim, Hassan (2012)
In recent years, the High Performance Work Systems (HPWSs) has been deliberated among the academicians and business players within the industries. Unfortunately, the study on this issue has been, mostly focus on the big size organization and conglomerates. Considering this phenomenon, it has created a high level of desire and curiosity to conduct a study on HPWSs in the sector of cooperatives. After considering all factors, Angkatan Koperasi Kebangsaan Malaysia Berhad (ANGKASA) has been selected as the case under study, because of its size, number of employees, nature of business and role in the cooperatives movement in Malaysia.In this study, human resource practices and organizational climate have been selected as the independent variables, while the high performance work systems, as a dependent variable. They will be tested in order to determine whether there is a relationship or influential forces among them. For the purpose of data analysis, a survey had been done to the employees of ANGKASA, by using the Simple Random Sampling. The analysis shows that there is a relationship between organizational climate and human resource practices with the high performance work systems towards ANGKASA.The number of questionnaire distributed were 450, where 260 employees had returned their questionnaire which consists of 58%.The correlation coefficient for the Organizational Climate for communication and Decision Making is 0.52, p<0.00, Bureaucracy is -0.22, p<0.00 and Work Methods is 0.56, p<0.00 for the organizational climate. While for the human resource practices, the pearson correlation for Training and Development is 0.66, p<0.00, Compensations is 0.56, p<0.00 and benefits is 0.59, p<0.00. Thus, it is crucial for the organization to put a great emphasize on the significant roles played by these two variables in high performance work systems.